A Systems study on the Bureau of Posts (ADC, DSMDC, FSMDC and MTS) - Lansañgan, Jacquenelle Anne G.; Lorenzo, Deborah C.; Ocampo, Jerome S.; Savella, Ronilo A.; Siriban, Anna Bella D. (College of Engineering, 1983)
Although this is a systems study on the Bureau of Posts' three main distribution centers (ADC, DSMDC and FSMDC) and the Motor Transport Section, it focuses on the Airmail Distribution Center since it was found to be a challenging design area. A system for ADC was designed to increase the efficiency and effectiveness of its mail processing. This study highlights the proposed specifications on the number and type of equipment and facilities, manpower reallocation, layout, workflow and systems and procedures. PROBLEM: Delay in Mail Processing. RECOMMENDATIONS: 1) Reallocate manpower within and/or between sections to level out manpower productivity according to mail volume handled by each section; a. Decrease manpower in RAS and reallocate to APS or FADS or OAS; b. Increase manpower in NAMDU, MMDU, and FARU coming from DAU and/or RAS; 2) Revise present layout; 3) Change number and type of equipment in ADC; 4) Incorporate lock box innovation in RAS; 5) Provide delivery pushcarts (at least one per section) in APS for better materials handling; and, 6) Improve sorting methods in APS. Lastly, we also proposed the planned systems change and implementation which were carefully laid down to the detail of activity specification and schedules.